Objectives and modern techniques in pea (Pisum sativum L.) breeding in Argentina: A review - Esposito, Maria Andrea; Garcia, Araceli Nora; Guindon, María Fernanda; Cazzola, Federico; Bermejo, Carolina J.; Gatti, Ileana (Ediciones INTA, 2024)
Pea is considered an essential component of sustainable farming systems. The main objective of pea researchers in Argentina and worldwide is to improve yield components and composition of the seed to enhance nutritional characteristics. Breeding programs that use conventional and nonconventional techniques are a very important tool to develop new varieties that can be used more efficiently in production systems but also adapt to changing market needs.